Життєвий цикл підприємства як фактор інвестиційної привабливості в умовах економічної турбулентності - Карпенко, А.; Пожуєв, Д. (Економічний вісник Донбасу, 2025)
Стаття присвячена дослідженню взаємозв'язку життєвого циклу підприємства та його інвестиційної привабливості в умовах економічної турбулентності 2020-2025 років. Проведено систематичний аналіз теоретичних засад життєвого циклу організацій від класичних моделей Грейнера та Адізеса до сучасних кількісних методів Дікінсона. Розкрито асиметричний вплив економічної турбулентності на підприємства різних стадій: медіанне виживання становить 27-35 днів для стадії впровадження проти 55-65 днів для зрілих організацій. The article examines the relationship between enterprise life cycle and investment attractiveness under economic turbulence conditions of 2020-2025. A systematic analysis of theoretical foundations of organizational life cycles is conducted, from classical models of Greiner and Adizes to modern quantitative methods of Dickinson. Empirical analysis is based on data from 351 Pakistani companies and 5,800 American enterprises, confirming U-shaped dependence of investment efficiency on development stage: from -0.0315 at introduction stage to 0.0431 at maturity stage. The asymmetric impact of economic turbulence on enterprises at different stages is revealed: median survival is 27-35 days for introduction stage versus 55-65 days for mature organizations. A Combined Investment Attractiveness Index (CIAI) is developed, integrating stage-specific characteristics with turbulence factors, ESG criteria, and digital maturity. Conceptual recommendations are proposed for investors regarding differentiated portfolio formation, for enterprises - attractiveness enhancement strategies depending on development phase, and for regulators - differentiated business support programs. The study contributes to corporate finance theory by substantiating the necessity of differentiated approaches to investment attractiveness assessment based on systematic interaction between enterprise life cycle stage and economic turbulence level.